Interactive Mobile Technologies on Civic Education Learning in Higher Education - Japar, Muhammad; Kardiman, Yuyus; Raharjo, Raharjo; Fadhillah, Dini Nur; Syarifa, Syifa (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study aims to describe the process of developing mobile learning on social tolerance material in higher education. Data collection was carried out using the Instructional Development Institute model Grabowski. The control class learning outcomes of 40 students get an average value of 73.25, while the experimental class learning outcomes of 40 students get an average value of 83.25. Furthermore, to find out the significance of the differences in learning outcomes between the two classes, a t-test was performed by conducting a normality test and a homogeneity test. Significant value is obtained for the control class of 0.153 and the experimental class of 0.601, so it can be concluded that the data are normally distributed because > 0.05.